Influência da expansão agrícola sobre a perda de solo no estado de Goiás - Pena, Diogo Silva (2020)
The growing establishment of agricultural activities based on the current intensive production models has accentuated several environmental problems, and an understanding of the dynamics of the occupation of the cerrado in relation to vegetation cover and its relationship with environmental impacts is fundamental to understand these problems. This study seeks to contribute to the knowledge regarding the dynamics of soil losses in the state of Goiás by verifying from mapping how this occupation occurred, in addition to analyzing the consequences of this occupation in relation to erosion processes, seeking to understand whether the rate of Soil loss has increased, and what type of occupation has generated more soil loss according to the soil loss prediction model known as the Universal Soil Loss Equation (USLE). Thus, the objective of this thesis is to evaluate the consequences of the occupation of the state of Goiás on soil losses between the years 1985 and 2017. It was observed that there was a great expansion of agricultural activities in the State of Goiás, causing significant changes in land use and occupation throughout the territory of Goiás, which according to EUPS caused an increase in soil erosion rates between the years analyzed. The average soil loss across the state of Goiás was 17.95 Mg/ha, with the highest value being observed in 2008 (22.59 Mg / ha), and the lowest value observed in 1990 (12.07 Mg/ha).